"We survived the pandemic together": The impact of the COVID-19 pandemic on Canadian families living with chronic pain. Issue 2 (30th July 2023) - Killackey, Tieghan; Soltani, Sabine; Noel, Melanie; Birnie, Kathryn A.; Choinière, Manon; Pagé, M. Gabrielle; Dassieu, Lise; Lacasse, Anaïs; Lalloo, Chitra; Poulin, Patricia; Ali, Samina; Baerg, Krista; et al.
ABSTRACT: Introduction: Pediatric chronic pain is a significant problem in Canada, affecting one in five youth. This study describes the impact of the pandemic on the experiences of Canadian families living with chronic pain through interviews with youth living with chronic pain, parents, and siblings. Methods: Employing a qualitative descriptive design, in-depth semistructured interviews were completed with Canadian youth living with pain, as well as parents and siblings. Participants were not required to be related. Interviews were analyzed using a reflexive thematic analysis approach. Results: Forty-four interviews were completed with 14 parents, 19 youth with chronic pain, and 11 siblings from across the country. Three key themes were developed: (1) absorbing and shifting: the toll of the pandemic on the family system (e.g., loss of coping mechanisms, shifting roles to respond to the pandemic), (2) social ambiguity and abandonment (e.g., social sacrifice and abandonment by the health care system), and (3) building community resilience: familial adaptation to the pandemic (e.g., family cohesion, confidence, and self-management). Discussion/Conclusions: Youth, parents, and siblings reported that the pandemic impacted coping strategies across the family system. These results outline the challenges youth experienced managing their pain and overall health throughout the pandemic and the resilience built within families during this time. Going forward, it would be relevant to examine how racialized and structurally marginalized youth with chronic pain and their families experienced the pandemic. Future research should examine how unexpected benefits of the pandemic (e.g., increased confidence and self-management) may be sustained into the future.